1987
DOI: 10.1021/ie00061a008
|View full text |Cite
|
Sign up to set email alerts
|

Ozone decomposition in water: kinetic study

Abstract: Kinetic studies on ozone decomposition in water were performed over a range of temperatures from 10 to 40 °C and pH rangp from 2.5 to 9. The ozone decomposition rate was determined in eq 24. This expression is supported by a reaction mechanism. The second term is negligible, at pH values below 3, leading to a first-order kinetic expression. The direct ozone-water reaction and the hydroxide ion initiation step are the main causes of ozone decomposition. Experimental and calculated ozone concentrations agree wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
133
2
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(150 citation statements)
references
References 2 publications
13
133
2
2
Order By: Relevance
“…This dual character allows O 3 to react through two different mechanisms, namely, direct and indirect ozonation. Direct ozonation involves degradation of organics by the O 3 molecule under acidic conditions, while indirect ozonation results in the formation of hydroxyl radicals and occurs under basic conditions [426,427]. O 3 is also similar to permanganate in that it has a strong affinity for organic compounds containing carbon-carbon double bonds by forming unstable ozonide intermediates.…”
Section: Fenton Reactionmentioning
confidence: 99%
“…This dual character allows O 3 to react through two different mechanisms, namely, direct and indirect ozonation. Direct ozonation involves degradation of organics by the O 3 molecule under acidic conditions, while indirect ozonation results in the formation of hydroxyl radicals and occurs under basic conditions [426,427]. O 3 is also similar to permanganate in that it has a strong affinity for organic compounds containing carbon-carbon double bonds by forming unstable ozonide intermediates.…”
Section: Fenton Reactionmentioning
confidence: 99%
“…It is widely known [25][26][27][28] that both hydroxyl ion and hydrogen peroxide act as initiators of the ozone decomposition process in aqueous phase.…”
Section: Ozonation Of Nts In the Presence Of Activated Carbons 321mentioning
confidence: 99%
“…4, increased water temperatures led to increased Cr(VI) formation. Aqueous O 3 decomposition studies have indicated that higher temperatures lead to increased rates of ozone decomposition (Beltrán, 2003;Sotelo et al, 1987), hence higher concentrations of the more aggressive oxidation radicals, as discussed earlier.…”
Section: Temperature Effectmentioning
confidence: 85%
“…Although it was not the aim of this paper to establish the chemical reaction mechanism of the Cr-containing material oxidation to Cr(VI), possible reasons for the observations can be postulated. At low pH values aqueous O 3 decomposition is relatively slow (Lovato et al, 2009;Beltrán, 2003;Sotelo et al, 1987); hence chromium oxidation is mostly dependent on the ability of dissolved O 3 to serve as oxidant. Gurol and Singer (1982) specifically reported that the rate of ozone decomposition was slow and relatively insensitive to pH below pH 4.…”
Section: Ph Dependencementioning
confidence: 99%